2011
DOI: 10.1002/ajmg.a.33862
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity mapping identifies the Crumbs homologue 1 (Crb1) gene as responsible for a recessive syndrome of retinitis pigmentosa and nanophthalmos

Abstract: The association of retinitis pigmentosa (RP) and microphthalmia has been reported in a number of familial and isolated cases. Here, the results of genetic analysis in a familial case of early RP associated with nanophthalmos are described. Two affected sibs were ascertained from an endogamous population in Mexico. A genome-wide linkage analysis was performed by means of an Affymetrix 250K microarray. Five large regions of homozygosity were demonstrated. The largest interval comprised 15.08 Mb at chromosome 1q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Patients with CRB1 mutations belong to both categories. Predisposition of the CRB1 patients to keratoconus (McKibbin, et al, 2010; McMahon, et al, 2009) and implication for pigmented paravenous chorioretinal atrophy (McKay, et al, 2005) and nanophthalmos (Zenteno, et al, 2011) have also been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Patients with CRB1 mutations belong to both categories. Predisposition of the CRB1 patients to keratoconus (McKibbin, et al, 2010; McMahon, et al, 2009) and implication for pigmented paravenous chorioretinal atrophy (McKay, et al, 2005) and nanophthalmos (Zenteno, et al, 2011) have also been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Other ocular findings associated with pathogenic CRB1 variants include macular atrophy, pigmented paravenous chorioretinal atrophy, and a predisposition to keratoconus and nanophthalmos [den Hollander et al, 2004;McMahon et al, 2009;Henderson et al, 2010;Zenteno et al, 2011;Bujakowska et al, 2012;Pellissier et al, 2015]. CRB1 mutations may also be a rare cause of cystoid macular edema, a condition that has responded favorably to topical carbonic anhydrase inhibitors [Tsang et al, 2014;Wolfson et al, 2015].…”
Section: Clinical Phenotypementioning
confidence: 99%
“…The frequency of CRB1 mutations in patients with macular nummular pigmentation was not available due to the unavailability of the frequency of this fundus change in patients analyzed in previous studies. However, macular nummular pigmentation is rarely observed in patients with mutations in other genes, although it has been described in different studies in a number of patients with CRB1 mutations (9,16,24,25,(35)(36)(37). Therefore, it may be considered a characteristic indication for CRB1-associated retinal dystrophy.…”
Section: Discussionmentioning
confidence: 99%